2022
DOI: 10.3390/jcm11133680
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Pulmonary and Extra-Pulmonary Traits between Women and Men with Chronic Obstructive Pulmonary Disease

Abstract: Background: Evidence suggests sex-related differences in chronic obstructive pulmonary disease (COPD). Whether these differences are reflected in the prevalence of treatable traits remains unknown. Methods: Two samples of patients referred to secondary (n = 530) or tertiary care (n = 2012) were analyzed. Men and women were matched for age, forced expiratory volume in 1 s and body mass index. Sex-related differences were tested using t-tests, Mann-Whitney U, or chi-square tests. Results: Frequent exacerbations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Moreover, Souto-Miranda et al . [ 29 ] showed that women suffer more activity-related dyspnea, severe hyperinflation, frequent exacerbation and hospitalization, which could explain why women were more frequently referred for PR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Souto-Miranda et al . [ 29 ] showed that women suffer more activity-related dyspnea, severe hyperinflation, frequent exacerbation and hospitalization, which could explain why women were more frequently referred for PR.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to men, women with COPD have a lower quality of life, face a more rapid decline in lung function [27] and more frequent anxiety and depression, which could lead to higher healthcare consumption [28]. Moreover, Souto-Miranda et al [29] showed that women suffer more activity-related dyspnea, severe hyperinflation, frequent exacerbation and hospitalization, which could explain why women were more frequently referred for PR. We found that patients who were older, who required more oxygen or NIV or who had more comorbidities were significantly more likely to receive PR.…”
Section: Features Related To Pr Uptakementioning
confidence: 99%
“…Researchers have previously found that male and female patients have significant differences regarding disease severity, prognosis, and comorbidities. 32 , 33 COPD has traditionally been seen as a disease of older men, but in recent years its prevalence among female patients has steadily increased. Future studies are needed to focus more on women with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The study of S outo- M iranda et al . [ 33 ] showed that sex-related differences exist in treatable traits among patients with COPD. Most traits were more prevalent in women than men in patients referred to secondary and tertiary care, with differences being more extensive in tertiary care.…”
Section: Group 902: Physiotherapistsmentioning
confidence: 99%